THE STUDY OF URBANONYMS IN TURKIC STATES: HISTORICAL DEVELOPMENT, METHODOLOGY, AND SOCIOLINGUISTIC ANALYSIS - Mahmud Gayratovich Khursanov (International Journal of Literature and Language Studies, 2026)
Abstract: Urbanonyms—the names of intra-city geographical objects such as streets, squares, avenues, and quarters—serve as crucial linguistic, historical, and cultural repositories. In Turkic states, urbantoponymic systems reflect centuries of historical transformations, shifting political ideologies, and deep-seated cultural heritages. This article examines the development of urbanonymic research across major Turkic nations, focusing primarily on Uzbekistan, Turkey, Kazakhstan, Azerbaijan, and Turkmenistan. By synthesizing structural-semantic, historical-comparative, and sociolinguistic methodologies, this study maps out how these nations have documented and analyzed their urban spaces. The results reveal that while early research focused heavily on etymological and historical inventories, contemporary Turkic onomastics increasingly addresses the sociolinguistic impacts of de-Sovietization, globalization, and national identity construction. The analysis underscores how urban naming practices function as tools for ideological legitimization and cultural preservation across the Turkic world.